Optimalisasi Program Desa Bahasa Banjarrejo Kecamatan Batanghari Kabupaten Lampung Timur Melalui Komunitas English Training and Gathering (ESTAGE) - Andianto Andianto; Kuryani Kuryani; Yasmika Baihaqi; Silvia Oprista; Muhammad Djorgi (Pusat Pengabdian Masyarakat (PPM) Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Institut Agama Islam Negeri (IAIN) Metro, 2023)
Learning and mastering English in nowadays is important. Mastering English as the international language gives some benefits. They are getting some important job, accessing to multiple culture, enabling us to travel around the world etc. Therefore, Banjarrejo, a small village in East Lampung, has a program to help societies to get an easy access to learn English in this village. The purpose of this study is to optimize the English language village’s program of Banjarrejo by 1) building English language community; 2) Enhancing human resources’ English skill; 3) providing place, material and media used in English community. This study is applied by using Asset-Based Community Development (ABCD). The results of this this study are formed: 1) English Training and Gathering (ESTAGE) as a community in learning English; 2) human resources who teach and facilitate societies in learning English; and 3) some facilities in learning English for community such as place, location, learning material, and media.